2012
DOI: 10.1038/hr.2011.228
|View full text |Cite
|
Sign up to set email alerts
|

Myofibrillogenesis regulator 1 induces hypertrophy by promoting sarcomere organization in neonatal rat cardiomyocytes

Abstract: Human myofibrillogenesis regulator 1, a novel 17-kDa protein, is closely involved in cardiac hypertrophy. We studied the molecular mechanism that links MR-1 to hypertrophic response. Hypertrophic hallmarks such as cell size and [3H]-leucine incorporation were significantly increased when MR-1 was transfected into cardiomyocytes for 48 h. However, sarcomere organization was promoted when MR-1 was transfected for 8 h. The finding that cardiac hypertrophy was induced long after increase of sarcomere organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 25 publications
(38 reference statements)
4
37
0
Order By: Relevance
“…It is closely associated with F-actin polymerization in neonatal rat cardiomyocytes [8,9] and the human liver cancer cell line HepG2 [10]. In the present study, MR-1 expression was reduced in I/R-treated rat kidney and H/R-treated HK-2 cells.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…It is closely associated with F-actin polymerization in neonatal rat cardiomyocytes [8,9] and the human liver cancer cell line HepG2 [10]. In the present study, MR-1 expression was reduced in I/R-treated rat kidney and H/R-treated HK-2 cells.…”
Section: Discussionsupporting
confidence: 49%
“…Samples containing 50 μg of protein were prepared and separated on 8-12% acrylamide gels and transferred to nitrocellulose membranes and blocked with 5% BSA in Tris-buffered saline Tween (20 mmol/l Tris-HCl, pH 7.5, 137 mmol/l NaCl, and 0.1% Tween 20). Membranes were incubated with antibodies against MR-1 (1:100) [9], MLC-2 (1:1,000; Abcam), pan-actin (1:500; Cell Signaling Technology, USA), and GAPDH (1:500; Abcam) overnight at 4°C. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To quantify the size of imaged cardiomyocytes, the space between each striation (illustrated by the distance between myomesin bands stained green and actin bands stained red) was accepted as 2um as previously described (Wang X et al, 2012;Klabunde R, 2007 Previous studies have shown that GATA4 activation by phosphorylation of serine 105 occurs during hypertrophic-induced pathways (van Berlo et al, 2001). In order to study our first aim in understanding the roles of GATA4 and CARP within such hypertrophic pathways, NRVMs were stimulated with PE or 7% FBS hypertrophic-inducing agents.…”
Section: Aim Two Immunofluorescencementioning
confidence: 99%